Developing critical thinking skills in computer-aided extended reading classes - Mat Daud, Nuraihan; Husin, Zamnah (Blackwell Publishing Ltd., 2004)
One of the skills that can be taught in an English proficiency class that adopts literary texts for teaching the language is critical thinking. The background, characters and their motives are among those that invite critical inquiry and interpretation. Although it has been claimed that discussing literary texts in the traditional way can help develop students' critical thinking skills, it is yet to be proved whether the use of a teaching aid can help the process. This study is, therefore, carried out to see if the use of computer software can help to develop such skills. It specifically looks at the potential of a literary text, Othello, and a concordancer in developing and enhancing critical thinking abilities of 40 English as a Second Language (ESL) students at the International Islamic University Malaysia. An experimental study was carried out, where an experimental group was exposed to text analysis using a concordancer whilst the control group analysed the text manually. The Cornell Critical Thinking Test was used to analyse the critical thinking ability of the students. The experimental group outperformed the control group in all the subscales measured, but the percentage of variance in the scores was low.